Utilization of Moodle in Teaching Undergraduate Students in West Africa - Kalyan Kumar Sahoo; Padma Charan Mishra; Rayalacheruvu Venkatamuni Reddy (National Research Mordova State University, 2020)
Introduction. Teaching pedagogy has become more advanced and techno friendly. The goal of this study is to inspect effectiveness of e-LMS (learning management system) prevalent for students of West African University, mainly at Private University Colleges. Materials and Methods. The samples were collected from Ghana, Nigeria, Sierra Leone, Togo and Benin. The research design is based on a survey method. Data were collected from 435-undergraduate students using questionnaires out of which 410-were found useful. Results. The result hints towards enhancing infrastructure for technology, more seminars and encouraging students to use the same. Discussion and Conclusion. Efficient use of LMS ought to be on obligatory institutional objectives and policies. The study recommends integration of LMS in curricula of undergraduate students of West African countries. The study further recommends efficient and useful information technology education to be made mandatory institutional policy for students and criteria for getting accreditation for organization.